KEBEBASAN HAKIM DAN PROBLEMATIKANYA DALAM SISTEM PERADILAN INDONESIA - Abdul Latif (Jurnal Hukum dan Peradilan, 2013)
Indonesian justice system is not fully functioning because there-rules and regulations that do not run as it should and there is a need to ensure greater freedom sanction judges in performing their duties. Public confidence in the judiciary should be restored. To strengthen the justice system needs to be guaranteed freedom of judges. Human resources need to be increased both its integrity and mastery of knowledge in particular substantive legal or formal. Modernization of the administration of justice would be better facilitate the course of justice will grow back confidence to the judiciary, but now is not optimal functioning to complete the administration of justice as is the accumulation of decisions that have not come to those seeking justice. Justice seeker the right to obtain justice freely and impartially, to be treated the same as fellow seekers of justice, and to obtain a decision within a reasonable, simple and low cost is a basic need for every seeker of justice. There needs to be increased in the direction of the change or shift from "the judge is bound" to the "independent judge", of "justice under the law" toward "justice according to the judge as set out in its decision, of thinking with reference to the system in the direction of thinking with reference to the problem. Keywords: Freedom of judges, Problems, Indonesian Justice System.